Celts and the classical world - Rankin, H. D. (Routledge, 1996)
This book provides a thoroughly researched and clearly presented picture of those Celts who strayed into the classical world and of the fringe Celtic communities at the moment when they were overrun and assimilated by Rome. -- THES.